2005
DOI: 10.1002/mus.20330
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of muscle receptors in proprioception?

Abstract: The role of muscle afferents is discussed in terms of their contribution to kinesthesia, the senses of position and movement of the limbs. It is argued that muscle spindles are not well suited as position sensors, on several grounds. Yet we know from muscle vibration experiments that they do contribute to kinesthesia. A number of recent experiments have shown that positional information is of particular significance to the central nervous system. In other experiments it has been demonstrated that a disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 35 publications
3
117
0
7
Order By: Relevance
“…No study was found that examined age-related changes in the Golgi tendon organ. The present review is focused on muscle spindles because it is the major mechanoreceptor involved in proprioception [39,53,54] and because the proprioception changes induced by physical activity seem to be related at peripheral level with muscle spindle adaptations. The central component involves internal feedback loops that transmit information between and within sensory and motor areas [39,44].…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 99%
“…No study was found that examined age-related changes in the Golgi tendon organ. The present review is focused on muscle spindles because it is the major mechanoreceptor involved in proprioception [39,53,54] and because the proprioception changes induced by physical activity seem to be related at peripheral level with muscle spindle adaptations. The central component involves internal feedback loops that transmit information between and within sensory and motor areas [39,44].…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 99%
“…In the present study, there was no difference in iEMG, which has been interpreted to reflect central motor command , between the two protocols. Furthermore, although it has been suggested that the relationship between central motor command and sense of effort is altered by peripheral information concerning the state of the contractile apparatus (Carson et al, 2002;Proske, 2005), states of the working muscle were similar in the two protocols in the present study as mentioned above. Thus, both central motor command and peripheral state must have been similar for both protocols and, as a result, there could be no difference in the sense of effort that is estimated from RPE between the two protocols.…”
Section: Discussionmentioning
confidence: 42%
“…Although the sense of effort is believed to derive from a copy (efference copy/corollary discharge) of the central motor command (Sperry, 1950;Von Host, 1954), it has recently been suggested that somatosensory feedback from the working muscles during exercise modulates the central motor command (Williamson et al, 2006;Matsuura et al, 2006Matsuura et al, , 2007 and that the relationship between central motor command and sense of effort is altered by peripheral information (Carson et al, 2002;Proske, 2005). These collectively suggest that during actual exercise afferent signals from the working muscles may affect the formation of the sense of effort.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that a number of afferent signals from peripheral organs to the CNS mediate sense of fatigue (11) and sense of effort is thought to arise centrally as a result of a corollary discharge of a motor command signal (14), RPE for overall body and legs did not follow changes in RMS and blood [La -]. This inconsistency may be explained by an idea proposed by Lambert and colleagues (5 Care must be taken in interpreting the results for SEMG activity.…”
Section: Discussionmentioning
confidence: 99%